Antimicrobial activity of two brazilian commercial propolis extracts - Giovanna Pires da Silva Ribeiro Rezende; Fabiana Cristina Pimenta; Luciane Ribeiro de Rezende Sucasas Costa (Universidade Estadual de Campinas, 2015)
The antimicrobial activity of propolis extracts is well documented, but little is known about the antimicrobial properties of commercial products containing propolis, since these vary according to the geographical region in which the propolis is obtained. This study evaluated the antimicrobial activity of two samples of commercial propolis on 26 species of microorganisms obtained from ATCC and some wild strains: Gram-positive cocci and bacilli, and Gram-negative rods and yeasts. The tested products were two samples of Brazilian commercial propolis from Apis Flora™: 11.0% ethanolic extract of propolis (EEP) and Propomax™ 11.0% extract of propolis without alcohol (EP). Antimicrobial activity was determined by the agar diffusion technique, well method. MIC was determined for Staphylococcus sp. and Streptococcus mutans using the method of broth dilution with the propolis extract in serial concentrations. EEP and EP showed antimicrobial activity against all tested bacteria and yeasts, having a more pronounced action against Gram-positive bacteria and Candida albicans ATCC 10231, and a less evident activity against Gram-negative and Candida albicans FT2010. For S. mutans, the EEP MIC ranged from 8.8 to 4.4 mL of propolis, and the EP MIC, from 4.4 to <1.1 mL. For Staphylococcus sp., the MIC of both extracts was <1.1.